The Use of Intra‐Operative Endoscopy in Dogs and Cats for the Removal of Gastrointestinal Foreign Bodies: Five Cases (2014–2015) - Inbar Israeli (Veterinary Medicine and Science)
ABSTRACT Objectives We report the use of intra‐operative endoscopy, termed here ‘surgically‐assisted endoscopy’. The procedure spares a gastrotomy, therefore, shortening anaesthetic time, minimising potential complications and resulting in a quicker and less painful recovery. Methods Four dogs and one cat requiring surgical celiotomy for various conditions were treated. In all animals, a gastrointestinal foreign body (FB) was located at surgery. During the surgery, with the patient still in dorsal recumbency and the abdomen still open, in lieu of gastrotomy, the animals had their FBs removed via endoscopy, sparing a gastrotomy procedure and its potential complications. Results In all five cases, a gastrotomy was avoided and the FBs were successfully extracted using the endoscope. Only one minor complication was seen intra‐operatively and none at short‐term follow‐up. Clinical Significance Although prognosis after gastrotomy is considered excellent, potential complications still exist and include haemorrhage, intra‐operative spillage, peritonitis and post‐operative dehiscence. Alternatively, endoscopy negates many of those possible complications and shortens anaesthesia time. In many cases of gastric FBs, or where intestinal FBs can be safely manipulated into the stomach, surgically assisted endoscopy could be considered a viable and potentially preferred option to gastrotomy.